The Great Founder of Medical Science - Ismoilov Isroil; Asadov Rovshan; Asadova Kamilla (Zien Journals, 2023)
Great scientists are not born, they become in the process of life. In fact, every person from birth is endowed with certain talents, but not every one of them has an unusually strong character that moves them towards the achievement of goals.
Keywords: achievement; unusually; moves; goals